Pertumbuhan Awal Ayam Merawang yang Dipelihara bersama Ayam Broiler - Sri Yunianti Putri Koes Hardini (LPPM Universitas Terbuka, 2004)
Kampong chickens have a lot of varieties spreading out all over Indonesia, and becoming everybody’s favourites, however, it has low productivity. Meanwhile, broiler chickens who have high productivity has certain level of immunity to a desease. Chickens have a nature of immitation. From this, a research has been developed to increase the productivity of kampong chickens in term of the increase of their body weigh by comparison of M7B3 (kampong chickens 7 and broiler 3), M5B5 (kampong 5 and broiler 5), M3B7 (kampong 3 and broiler 7) and kampong control M10, and broiler control B10. From this mixture, we can see their eating behavior that has on impact upon the kampong chickens’body weight from those that are DOC to those that are 6 weeks. Infact, this mixture does not make their growth (the increase of their weight) defferent. However, M3B7 shows good combination and the increase of their weight on the part of kampong chickens on average. This result may be caused by the narrow combination of the mixture. Heig mortality is experienced by the broiler chickens when they attacked by Berak Kapur desease. This proves that Kampong chickens’ immunity is better than that of broiler chickens.